การศึกษาเปรียบเทียบการนำเสนอภาพลักษณ์ของตลาดหลักทรัพย์ในสมัยรัฐบาลชวน หลีกภัย กับ สมัยรัฐบาลบรรหาร ศิลปอาชา โดยหนังสือพิมพ์ - วรรษมน เสาวคนธ์เสถียร (จุฬาลงกรณ์มหาวิทยาลัย, 1996)
The main purpose of this study was to compare the image of The Stock Exchange of Thailand in Thai newspapers during Chuan administration and Banharn administration (September 22,1922-November 25, 1966) The study was done through the analysis of the content of 8 newspapers, i.e.: Thairath, Daily News, Siam Post, Matichon, Krungthep Thurakij, Phujadkarn Raiwan, Prachachart Thurakij and Tharn Settakij, with the total of 1,744 copies. The study found that image of The Stock Exchange of Thailand during the two administrations as presented most by newspapers was negative. The negative issues presented most were the social responsibility of the Stock Exchange of Thailand and its effect on economic system of the country, the inefficiency of administration and the image of the administrators. Meanwhile, the positive issues presented most were the increase in efficiency of administration and potentiality of organization in performance, human resources and technology. The image was mostly presented in the forms of news, analysis, article, report and interview respectively. When the two periods were compared, the image of the Stock Exchange of Thailand during Chuan administration was presented in positive and negative directions equally while during Banharn administration it was presented in the negative direction more than the positive direction.